Remediation efficiency of Cd-B[a]P combined polluted soil by Sedum alfredii - LI Ting-qiang; DONG Zeng-shi; JIANG Hong; LI Bing; YANG Xiao-e (浙江大学学报. 农业与生命科学版, 2011)
Remediation efficiency of cadmium (Cd) and benzo [a] pyrene (B[a]P) combined polluted soil by Sedum alfredii Hance was studied using pot experiment under controlled temperature and natural light during cultivation. The results showed that the growth of hyperaccumulating ecotype (HE) of S. alfredii was inhibited under high B[a]P level (25 mg·kg-1), whereas the biomass of non-hyperaccumulating ecotype (NHE) decreased significantly due to Cd toxicity. When treated with low Cd (1 mg·kg-1), the root biomass of both HE and NHE were increased by 5 mg·kg-1 B[a]P. Cadmium concentration in the shoot of the HE was much greater than the NHE and was not influenced by B[a]P supply level. The B[a]P concentrations in both shoot and root of both ecotype of S. alfredii were controlled by B[a]P level in the soil instead of Cd. The removal efficiency of Cd from Cd-B[a]P combined polluted soil by the HE was much greater than the NHE, however, significant decrease of Cd removal efficiency was observed with treatment of 25 mg·kg-1 B[a]P. The removal efficiency of B[a]P from unplanted soil was 43.7%, whereas it was increased to 58.2% after planted with both ecotypes of S. alfredii. All the results above suggest that hyperaccumulating ecotype of S. alfredii has great potential for phytoremediation of Cd and B[a]P moderately contaminated soil.